Toward a Natural Theology of Abundance: Reorientation to a Sacramental Reality - Thiessen, Annalea Rose (Religions, 2023)
This paper presents the Christian incorporation and transformation of the philosophical understanding of the relation between the material and immaterial. This transformation centers on the Incarnation of Christ, which changes both the relation or contact between the material and immaterial realms, and human knowledge concerning the immaterial divine presence in material reality. More than a descriptive, historical account, the paper is primarily a conceptual presentation that retrieves the historically early thought of Irenaeus of Lyons and Athanasius of Alexandria to argue for a theological account of sacramental reality. Drawing on the metaphysical function of sacraments—themselves “visible signs of invisible grace”—which convey that there is more to material reality than meets the eye, I argue that this “more” implies what I call “a theology of abundance” that pertains to the whole of created reality, in the abundant nature of creation and of the human being in particular, and especially apparent in human knowing. The implication of such a theology of abundance is a comprehensive reorientation of human being, knowing, and expression in response to the invisible presence of the divine in visible, sacramental reality.